The effect of early childhood development program attendance on future school enrollment and grade progression in rural North India - Gautam Hazarika; Vejoya Viren (Institute for the Study of Labor (IZA), 2010)
This paper examines the effect of prior participation in early childhood developmental programs, considered endogenous, upon 7-19 years olds' school enrollment and grade progression in rural North India. It hopes both to extend to less developed countries recent influential research on the long-term benefits of early childhood interventions in the United States, and to make a case for the inclusion of such interventions amongst developing nations' policy initiatives toward expanding schooling. Analysis of data from the World Bank's 1997-98 Survey of Living Conditions in Uttar Pradesh and Bihar yields the findings that early childhood developmental program attendance at ages 0-6 raises the probability of school enrollment among average 7-19 year olds by 31 percentage points, and that this beneficial early experience also significantly hastens students' grade progression.
Keywords: I21; O12; O15; 330; early childhood development; less developed country; India; schooling; Familienpolitik; Wirkungsanalyse; Kinder; Bildungsverhalten; Bildungsniveau; Bihar; Uttar Pradesh; Indien